Propuesta de modelo de proyección financiera para la Compañía OPSI de Colombia S.A.S en los próximos 5 Años (2024)
The degree work entitled "Proposal for a Financial Projection Model for the Company OPSI de Colombia S.A.S in the Next 5 Years" focuses on the development of a comprehensive financial model that allows the company OPSI de Colombia S.A.S to anticipate and plan its economic performance in the near future.